Answer:
x=1, y=-4. (1, -4).
Step-by-step explanation:
y=-7x+3
y=-x-3
-------------
-7x+3=-x-3
-7x-(-x)+3=-3
-7x+x=-3-3
-6x=-6
6x=6
x=6/6
x=1
y=-1-3=-4
Answer:
x² + 4x + 3
Step-by-step explanation:
to find f(g(x)), substitute x = g(x) into f(x)
f(g(x)) = f(x + 2) = (x + 2)² - 1 = x² + 4x + 4 - 1 = x² + 4x + 3
The sum (addition) of t and 2 is equal to (=) 5 less than (subtraction) t
2 + t = t - 5
I know of two ways to solve quadratic equations. The first is through factoring. Let us take the example (x^2)+2x+1=0. We can factor this equation out and the factors would be (x+1)(x+1)=0. To solve for the roots, we equate each factor to 0, that is
x+1=0; x+1=0
In this case, the factors are the same so the root of the equation is
x=1.
The other way is to use the quadratic formula. The quadratic formula is given as [-b(+-)sqrt(b^2-4ac)]/2a where, using our sample equation above, a=1, b=2 and c=1. Substitute these to the formula, and you will get the same answer as the method above.
Answer:
uh depends on the equations